Antacid maintenance therapy in the prevention of duodenal ulcer relapse. Issue 12 (December 1988) - Bardhan, K D; Hunter, J O; Miller, J P; Thomson, A B; Graham, D Y; Russell, R I; Sontag, S; Hines, C; Martin, T; Gaussen, L
Abstract : The effectiveness of antacid maintenance therapy in preventing duodenal ulcer (DU) relapse was investigated. Two hundred and fifty one asymptomatic patients with healed DU were stratified into smokers and non-smokers and randomised to receive for one year either placebo, or Maalox TC three tablets (81 mmol) at bedtime (hs), or Maalox TC three tablets in the morning plus three tablets at bedtime (bd) (162 mmol), or cimetidine 400 mg at bedtime. A double dummy technique was used to render the study double blind. In 176 patients evaluable for efficacy, the cumulative relapse at one year was: placebo 57%; Maalox TC hs 39%; Maalox TC bd 23%; cimetidine 25%. Maalox TC bd and cimetidine were equally effective and superior to placebo (p less than 0.01) and bedtime Maalox TC (p less than 0.04). The benefit of treatment was significant for the overall sample and for the subgroup of smokers. The results for the non-smokers also supported efficacy for these two treatments but, perhaps because of small sample sizes, these comparisons were not significant. All 251 patients were assessed for safety. Approximately half the patients in each treatment group had adverse events, leading to withdrawal in three, seven, 12, and four patients on placebo, Maalox hs, Maalox bd, and cimetidine respectively. Diarrhoea occurred in 12 patients in Maalox TC bd and eight in each other group. Serum magnesium concentrations were unchanged; aluminium concentrations were higher than baseline at six and 12 months in both antacid groups and at 12 months in the cimetidine group but the differences were not significant. Maalox TC three tablets bd are as effective as cimetidine 400 mg at bedtime in reducing DU relapse and both are superior to placebo.